The development of biomimetic tactile sensor for fine touch - Wei, Sun (2018)
Being inspired by the tactile sensing capability of human fingertip, a bio-inspired tactile sensor was fabricated to emulate similar functions of human fingers through mimicking mechanoreceptors embedded in the human skin. Surface roughness discrimination ability is the desired application of this fabricated artificial sensor. The success of surface discrimination of a tactile sensor could drive more developments and investigations in biomimetic robots, prosthetic limb and humanoid tactile sensing fields. Physiologically, when human explores surfaces, textures and different object shapes, these external induced physical stimuli would be detected and then converted into electrical impulses through various receptors, human brain could decode the electrical impulses into useful information such as the surface roughness and object shapes. To mimic this physic-electric-information process, in this project, a piezoelectric material called Polyvinylidene Difluoride(PVDF) and a strain gauge are used to mimic the receptors which convert physical stimuli to electrical change in voltage or resistance, subsequently, those electrical stimuli are then being amplified through a differential voltage amplifier up to a measurable level for further signal conditioning. A data acquisition system which mimics the human brain is used to do data collection and analysis, then all the numeric data is interpreted into useful information, that is, the surface roughness, Ra value. Therefore, the information generated could help to conclude the measurement accuracy of this fabricated sensor. Besides, different shapes of sensing transducer and fingertip molds were designed to investigate the effects of fingertip geometry and transducer location on the sensor measurement accuracy. Consequently, an optimal tactile sensor could be fabricated to achieve the highest level of measurement accuracy in surface roughness discrimination.